Endothelin-1 Lys198Asn and rs10478694 polymorphism in ischemic stroke. - Aslan, Orhan; Gurger, Mehtap; Atescelik, Metin; Kara, Murat; Sen, Askin; Alatas, Omer Dogan; Kargun, Kursat (Scientific Publishers India, 2017)
Objective: In this study, we aimed to investigate the relationship between ischemic cerebrovascular diseases and Lys198Asn and rs10478694 polymorphism of Endothelin-1 gene, a strong vasoconstrictor. Materials and Methods: Blood samples were isolated from 100 patients diagnosed with ischemic cerebrovascular diseases and Lys198Asn and rs10478694 polymorphism of Endothelin-1 gene from obtained DNAs by Real-Time Polymerase Chain Reactions Method (RT-PCR). Results: Forty-one patients in the patient group and 38 patients in the control group were found to be heterozygous for Lys198Asn. Thirty-nine patients in the patient group and 39 patients in the control group were found to be heterozygous for rs10478694. Lys198Asn was found to be homozygous mutant in 8 patients in the patient group and 9 patients in the control group. Rs10478694 was found to be homozygous mutant in 9 patients in the patient group and 7 patients in the control group. There was no significant difference in age and gender between patients with and without identified polymorphisms (p>0.05). In addition, smoking and alcohol use, presence of hypertension, diabetes mellitus, coronary artery disease and chronic obstructive pulmonary disease was found not to be correlated with positivity of gene polymorphism. Conclusion: Lys198Asn and rs10478694 polymorphism of Endothelin-1 gene was found not to be correlated with ischemic cerebrovascular diseases.
Keywords: Ischemic cerebrovascular disease; Endothelin-1; Lys198Asn; rs10478694